Slawni polacy. Wodzowie i zolnierze - Luterek, Grzegorz (Poznan : Podsiedlik, Raniowski i Spolka, 1998)
A short history of famous Polish military persons throughout Poland's history.
Keywords: Soldiers -- Poland -- Biography; Poland -- History, Military